2011
DOI: 10.1111/j.1537-2995.2011.03428.x
|View full text |Cite
|
Sign up to set email alerts
|

New platelet glycoprotein polymorphisms causing maternal immunization and neonatal alloimmune thrombocytopenia

Abstract: BACKGROUND Maternal immunization against low-frequency, platelet (PLT)-specific antigens is being recognized with increasing frequency as a cause of neonatal alloimmune thrombocytopenia (NAIT). STUDY DESIGN AND METHODS Serologic and molecular studies were performed on PLTs and DNA from two families in which an infant was born with severe thrombocytopenia not attributable to maternal immunization against known PLT-specific alloantigens. RESULTS Antibodies reactive only with paternal PLTs were identified in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 45 publications
(74 reference statements)
0
27
0
Order By: Relevance
“…DNA-based platelet typing [2] confirmed that the patient’s genotype was HPA-1b/b, HPA-2b/b, a combination found in about one in 2,500 African-Americans.…”
mentioning
confidence: 99%
“…DNA-based platelet typing [2] confirmed that the patient’s genotype was HPA-1b/b, HPA-2b/b, a combination found in about one in 2,500 African-Americans.…”
mentioning
confidence: 99%
“…Diagnosis of NAIT was considered to be confirmed when a maternal antibody was identified that recognized an HPA present in the father or, in rare cases, was specific for GPIV (CD36); other cases were considered to be “unresolved.” Detailed clinical information was available only on cases in which a paternal LFHPA antigen was identified in the Phase 1 study; histories in these cases were consistent with NAIT of varying degrees of severity. Some cases in which LFHPAs were identified in the Phase 1 study (see Results) have been described previously in a different context …”
Section: Methodsmentioning
confidence: 53%
“…MACE was carried out as described previously 28 . In brief, HEK293 cell lines stably expressing recombinant human CTL2-GFP (R154 or Q154) were sensitized with human HNA-3a antibodies (diluted 1:5), washed and lysed with 1.0% Triton X-100.…”
Section: Methodsmentioning
confidence: 99%